Review: Biogas Production Utilizing Indigenous Bacteria from Liquid Tofu By-product and Organic Botanical Food Waste in Small and Medium Enterprises (SMEs) - Karyn Gracia Hartono; Karla Katina Salim Nohkarsan; Caroline Noel Amaris Purnomo (JFCN: Journal of Food, Culinary, and Nutrition, 2026)
The increasing production of liquid tofu by-products and botanical food waste by SMEs highlights the need for sustainable waste management while providing significant potential for biogas generation. Liquid tofu by-products and organic botanical food waste have potential for biogas production, with a focus on the role of indigenous microbial in the process. This review aims to evaluate and synthesize current research regarding the utilization of liquid tofu by-products and botanical food waste for biogas generation, with particular emphasis on the role of indigenous microorganisms and the applicability of such systems in SMEs. This review was conducted by gathering information from articles retrieved from scientific databases using keywords such as biogas production, liquid tofu by-product, indigenous bacteria, etc. From the data collection process, the gathered information will be analyzed and synthesized to conclude. The reviewed studies indicate that co-digestion of liquid tofu by-products and botanical food waste can improve substrate balance, optimize the carbon-to-nitrogen ratio, and enhance methane production compared with single-substrate digestion. The findings suggest that small-scale biogas systems utilizing these waste streams could contribute to waste reduction, renewable energy production, and sustainable waste management in SMEs. In conclusion, combining liquid tofu by-products with botanical food waste can generate more biogas than the digestion of using vegetable waste alone